2016
DOI: 10.1017/s1366728916000791
|View full text |Cite
|
Sign up to set email alerts
|

The developmental trajectories of attention distribution and segment-tone integration in Dutch learners of Mandarin tones

Abstract: This study investigates how beginner and advanced Dutch learners of Mandarin process tonal information. An ABX task was adopted to investigate phonological discrimination of Mandarin tones and segment-tone integration in Dutch learners of Mandarin, with both native Mandarin and Dutch speakers (without tonal learning experience) as control groups. Results showed a developmental path in lexical tone processing. The beginner learners could not process tonal contrast adequately at the phonological level, and they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(74 citation statements)
references
References 51 publications
4
64
6
Order By: Relevance
“…for monosyllables (Pelzl et al, 2019), and other studies have also found strong-if not completely nativelike-L2 categorization of tones among more advanced learners (Ling and Grüter, 2020;Froud, 2016, 2019;Zou et al, 2017). While overall impressive, such results are not a claim for flawless L2 tone perception.…”
Section: Three General Explanations For L2 Tone Word Processing Difficultiesmentioning
confidence: 70%
See 1 more Smart Citation
“…for monosyllables (Pelzl et al, 2019), and other studies have also found strong-if not completely nativelike-L2 categorization of tones among more advanced learners (Ling and Grüter, 2020;Froud, 2016, 2019;Zou et al, 2017). While overall impressive, such results are not a claim for flawless L2 tone perception.…”
Section: Three General Explanations For L2 Tone Word Processing Difficultiesmentioning
confidence: 70%
“…Misidentification of Mandarin tones is common among naïve and novice learners (e.g., Wang et al, 1999;Alexander et al, 2005;Bent et al, 2006;Huang and Johnson, 2010;So and Best, 2010). For more experienced learners, tone identification and categorization abilities improve and many individuals approach native levels on categorization and identification tasks (Ling and Grüter, 2020;Pelzl, 2019;Shen and Froud, 2016;Tsukada and Han, 2019;Zou et al, 2017). Nevertheless, similarities between F0 contours among Mandarin tones can lead to confusions among some tones (e.g., in isolated syllables, Tone 3 may have a dipping contour leading it to resemble Tone 2).…”
Section: Introductionmentioning
confidence: 99%
“…This belief appears somewhat at odds with research that consistently shows beginning learners making quick gains in tone identification accuracy through focused training (e.g., Wang, Spence, Jongman, & Sereno, 1999). Similarly, while there are relatively few studies that examine more advanced L2 learners of tone languages, several suggest such learners can obtain a high degree of mastery in perceiving tones (Lee, Tao, & Bond, 2010; Zhang, 2011; Zou, Chen, & Caspers, 2016). However, these results do not necessarily rule out long-term difficulties related to L2 tone perception.…”
Section: Introductionmentioning
confidence: 99%
“…In light of previous findings on the learning of novel segmental contrasts, it is hypothesized that a similar effect of overnight consolidation will be found for the perceptual learning of Cantonese level tones by Mandarin listeners. Specifically, those listeners who are trained in the evening are expected to perform better than those who are trained in the morning in perceiving the level tones produced by a new talker and probably also by the trained talker, given a potentially greater difficulty of learning the target (three-way) tonal contrasts relative to (two-way) segmental contrasts [6163]. As discussed above, the magnitude of the overnight consolidation effect and underlying mechanisms may differ between the identification and discrimination tasks [15,19].…”
Section: Introductionmentioning
confidence: 99%